The Anti-Cancer Effect of Polyphenols against Breast Cancer and Cancer Stem Cells: Molecular Mechanisms - Ahmed Abdal Dayem; Hye Jin Choi; Gwang‐Mo Yang; Kyeongseok Kim; Subbroto Kumar Saha; Ssang‐Goo Cho (2016)
The high incidence of breast cancer in developed and developing countries, and its correlation to cancer-related deaths, has prompted concerned scientists to discover novel alternatives to deal with this challenge. In this review, we will provide a brief overview of polyphenol structures and classifications, as well as on the carcinogenic process. The biology of breast cancer cells will also be discussed. The molecular mechanisms involved in the anti-cancer activities of numerous polyphenols, against a wide range of breast cancer cells, in vitro and in vivo, will be explained in detail. The interplay between autophagy and apoptosis in the anti-cancer activity of polyphenols will also be highlighted. In addition, the potential of polyphenols to target cancer stem cells (CSCs) via various mechanisms will be explained. Recently, the use of natural products as chemotherapeutics and chemopreventive drugs to overcome the side effects and resistance that arise from using chemical-based agents has garnered the attention of the scientific community. Polyphenol research is considered a promising field in the treatment and prevention of breast cancer.